EGF Levels in Rattus norvegicus Induced with 40 ppm Formaldehyde for 1 Month in Relation to Nasopharyngeal Cancer - Putri, Gabriella Chrisanta Dwi Ananda; Wedayani, Anak Agung Ayu Niti; Yuliyani, Eka Arie; Partiwi, Sekar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Nasopharyngeal carcinoma (NPC) is one of the most common malignancies in the ENT department, with a high incidence in Southeast Asia. One of the major risk factors for NPC is formaldehyde exposure, which induces oxidative stress, chronic inflammation, and disruption of growth factors such as Epidermal Growth Factor (EGF). This study aims to analyze changes in EGF levels in Rattus norvegicus exposed to 40 ppm formaldehyde for one month to better understand the molecular mechanisms contributing to nasopharyngeal carcinogenesis. This experimental study measured EGF levels using the Enzyme-Linked Immunosorbent Assay (ELISA) method. Data were analyzed using the Kolmogorov-Smirnov normality test and a Paired T-Test to assess changes in EGF levels before and after treatment. The analysis showed a tendency for increased EGF levels after formaldehyde exposure; however, the difference was not statistically significant (p = 0.355). This suggests that one-month exposure to formaldehyde does not directly affect EGF expression in the tested tissue. This study found that 40 ppm formaldehyde exposure for one month did not significantly alter EGF levels. However, the observed trend in certain groups suggests that the effect of formaldehyde on EGF levels may be dose- and duration-dependent. Further studies with longer exposure durations and higher concentrations are needed to explore the link between formaldehyde exposure and nasopharyngeal carcinogenesis.